Anxiety and depression symptoms in women and men from early pregnancy to 3-months postpartum: parity differences and effects - Figueiredo, Bárbara (2011)
This study aimed to investigate both anxiety and depression symptoms from early pregnancy to 3-months postpartum, comparing women and men and first and second-time parents. Methods: A sample of 260 Portuguese couples (N=520), first or second-time parents, recruited in an Obstetrics Out-patients Unit, filled in the State-Anxiety Inventory (STAI-S) and the Edinburgh Post-Natal Depression Scale (EPDS) at the 1st, 2nd and 3rd pregnancy trimesters, childbirth, and 3-months postpartum. Results: A decrease in anxiety and depression symptoms from early pregnancy to 3-months postpartum was found in both women and men, as well as in first and second-time parents. Men presented less anxiety and depression symptoms than women, but the same pattern of symptoms over time. Second-time parents showed more anxiety and depression symptoms than first-time parents and a different pattern of symptoms over time: an increase in anxiety and depression symptoms from the 3rd trimester to childbirth was observed in first-time parents versus a decrease in second-time parents. Limitations: The voluntary nature of the participation may have lead to a selection bias; women and men who agreed to participate could be those who presented fewer anxiety and depression symptoms. Moreover, the use of self-report symptom measures does not give us the level of possible disorder in participants. Conclusions: Anxiety and depression symptoms diminish from pregnancy to the postpartum period in all parents. Patterns of anxiety and depression symptoms from early pregnancy to 3-months postpartum are similar in women and men, but somewhat different in first and second time parents. Second-time parents should also be considered while studying and intervening during pregnancy and the postpartum.